Analysis Of Factors Affecting the Quality of Audit Results at the Bengkulu Province Inspectorate Office - seftya dwi shinta (Jurnal Ekonomi, Manajemen, Akuntansi dan Keuangan, 2022)
The data used was primary data with auditors working in the provincial and municipal inspectorates in Bengkulu as the respondents. The sampling technique used the purposive sampling method with 30 respondents. The results showed that objectivity, integrity, work experience, competency, and ethics of auditor’s positively and significantly influenced the quality of audit results. While the variables of independency negative and significantly influenced the quality of audit results.